PENGARUH KOMPETENSI TERHADAP KINERJA DOSEN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Purba, Melfrianti Romauli (Jurnal Ekonomi Bisnis Manajemen Prima, 2023)
Universities are expected to be able to provide improvements in the quality of human resources so that they are able to carry out the tri dharma of higher education in a professional manner and the resulting performance can be satisfactory. Individual ability was one of the aspects needed in achieving satisfactory performance so that human resources need to be continuously developed. The objective of this research was to determine whether competence affects lecturer performance through job satisfaction as a mediating variable. This research was conducted on 142 lecturers at the Faculty of Economics, Universitas Prima Indonesia using simple random sampling and slovin techniques with a 5% allowance and the results were 105 respondents. Primary data collection techniques in the form of questionnaires and secondary data obtained through documentation studies. Data analysis techniques use quantitative data processed with the SPSS version 20, namely the t test and the coefficient of determination (R2). The results obtained in this study showed a significant influence between competency variables on job satisfaction, significant influence between competency variables on performance, influence between job satisfaction variables on performance, competency variable through job satisfaction had an influence on performance.